2015
DOI: 10.1007/s11357-015-9775-z
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature reduction extends lifespan via activating cellular degradation activity in an annual fish (Nothobranchius rachovii)

Abstract: Ambient temperature reduction (ATR) can extend the lifespan of organisms, but the underlying mechanism is poorly understood. In this study, cellular degradation activity was evaluated in the muscle of an annual fish (Nothobranchius rachovii) reared under high (30 °C), moderate (25 °C), and low (20 °C) ambient temperatures. The results showed the following: (i) the activity of the 20S proteasome and the expression of polyubiquitin aggregates increased with ATR, whereas 20S proteasome expression did not change; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…These CSPs could mediate certain protective effects of cooling during neurodegeneration and aging (Peretti et al 2015). Low temperatures can also stimulate the proteasome degradation pathway in fish, which may contribute to longevity (Lu and Hsu 2015). It is unclear how CSPs and the proteasome pathway are turned on by low temperatures.…”
Section: Temperature and Longevitymentioning
confidence: 99%
“…These CSPs could mediate certain protective effects of cooling during neurodegeneration and aging (Peretti et al 2015). Low temperatures can also stimulate the proteasome degradation pathway in fish, which may contribute to longevity (Lu and Hsu 2015). It is unclear how CSPs and the proteasome pathway are turned on by low temperatures.…”
Section: Temperature and Longevitymentioning
confidence: 99%
“…The core can be flanked by either one or two regulatory particles, RPs or 19S, which are responsible for the recognition and unfolding of polyubiquitinated proteins (Finley et al 2016). In the killifish species Nothobranchius rachovii, a linear inverse correlation is seen in muscle tissue between proteasome activity and ambient temperature, without a detectable change in proteasome amount (Lu and Hsu 2015). Also, raising the room temperature of mice housed at 22 to 30°C decreases in vitro measured proteasome activity from brown adipose tissue (Bartelt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with a report by Lu and Hsu, who found that a reduction in ambient temperature extends the lifespan of N. rachovii. Mechanistically, this effect was probably linked with an improvement in cellular degradation pathways, as evidenced by increased 20S proteasome activity, decreased levels of polyubiquitin aggregates, and increased expression of the macroautophagy indicator microtubule-associated protein 1 light chain 3 (LC3) [ 105 ]. Another intriguing factor affecting the lifespan of N. furzeri appeared to be the gut microbiota.…”
Section: Aging In the Fish Of The Genus Nothobranchiusmentioning
confidence: 99%